Spatiotemporal Characterization of Geophysical Signal Detection Capabilities of GRACE‐FO. Issue 1 (29th December 2021) - Peidou, Athina; Landerer, Felix; Wiese, David; Ellmer, Matthias; Fahnestock, Eugene; McCullough, Christopher; Spero, Robert; Yuan, Dah‐Ning
Abstract: The intersatellite range measurements between the Gravity Recovery and Climate Experiment Follow‐On (GRACE‐FO) satellite pair enable mapping time variations in Earth's gravity field. The Laser Ranging Interferometer (LRI) and Microwave Instrument (MWI) provide independent range measurements. We compare gravity fields derived from the two instruments. The LRI captures time‐variable gravity field signals up to 21 mHz (165 km half‐wavelength) globally, while MWI reaches frequencies up to 15 mHz (230 km). Time‐variable mass variations free from annual cycles and trends are sensed up to 15 mHz (LRI) and 11 mHz (320 km) (MWI). Both instruments are shown to be excellent tools for detection and monitoring of sub‐monthly geophysical signals. Along‐track global maps of sub‐monthly signals are expected to shed light on the high‐frequency behavior of a large number of geophysical processes. Plain Language Summary: Mass change is a fundamental observable for climate studies. The Gravity Recovery and Climate Experiment (GRACE) and GRACE‐FO satellite gravimetry missions track mass changes on a monthly basis for nearly 20 years. We are interested in characterizing the capabilities of the GRACE‐FO measurement system to observe mass change signals mapped in the time‐variable gravity field, in space, time and frequency domains. Analysis of the gravity fields retrieved using two independent ranging instruments on GRACE‐FO, the Microwave Instrument (MWI) and a novel Laser Ranging Interferometer (LRI), shows that the LRI consistently detects time‐variable gravity signals in higher frequencies (finer spatial scales) than the MWI. Additionally, we show that both instruments are very efficient in measuring sub‐monthly gravity field variations, mainly driven by ocean dynamics, hydrosphere and tides. A refined function that translates range acceleration measurements to surface mass estimates is also introduced and used to convert measured range accelerations over known watersheds to surface mass estimates. Key Points: We quantify the ability of the GRACE‐FO measurement system to measure geophysical signals in space and time The GRACE‐FO measurement system can provide global maps of sub‐monthly gravity signals driven by hydrosphere, tides, and ocean dynamics Laser ranging maps time‐variable gravity at finer spatial scales than microwave ranging